Selection of Heifers and Breeding Bulls for Reducing Calving Difficulties in the First Calvers: An Overview - Shah, Nadem; Sethi, Manisha; Kumar, Pratyush; Mohanty, Tushar K.; Dewry, Raju K.; Sarkar, Debajyoti; Gupta, Vinod K.; Soe, Aye; Bhakat, Mukesh (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Calving difficulty is associated with cow mortality, calf loss, veterinary and labor costs, and causes delayed return to estrus and lowerconception rate. Dystocia is common in heifers, and the frequency decreases with the increasing age of the cow. Farmers need toconsider both genetics and management factors in an attempt to reduce dystocia. Calf birth weight, the pelvic area of the dam and theirinterrelationships are major determinants of dystocia. The weight of the calf is governed by genetic, environmental and managementfactors. Genetic factors include sex, length of gestation, breed, inbreeding, and genotype. Non-genetic factors include age and parity ofthe dam, nutrition of the dam during various phases of gestation, and environmental temperature and humidity. Dystocia managementmust begin with a selection of heifer for mating with respect to the body weight of heifers, body condition score (BCS) and dam’s pelvicarea should be considered before heifer selection. Not only heifer selection but sire selection using an estimated breeding value forcalving ease should also be considered to lessen the dystocia rate in a herd. A combination of culling heifers with small pelvic areasand using bulls reported to be calving ease sire may reduce dystocia significantly. Apart from all these factors, genomic selection forreducing calving difficulties is a new tool for dystocia management.
Keywords: Calving ease sire; Heifer; Pelvic area